Using Tolkien’s Literature to Increase Student Understanding and Language Proficiency in English - Margrét Sara Guðjónsdóttir 1975- (2023)
In Iceland, there is a long history of teaching English. There was a major change when the language became a first foreign language from a second foreign language. That led to English being taught at an earlier stage of primary-level education. Globalization and technological development with more accessibility for people impacted English education in Iceland. This development in English education is one of the things that prompted this study. Other factors that prompted the study were the passion of the teacher to develop and enhance teaching principles. To create a learning environment where the students could approach language learning in a new and improved way. The students had the opportunity to be creative, participate in their education process, and receive diverse teaching methods in collaboration with the teacher. They should have a chance to learn English in a way the National Curriculum (2013) states they should. The theoretical approach in this study is teacher action research and using the teaching methods of CLIL. Specific content was integrated into teaching the English language in a course in a secondary school in Iceland. This was an elective English course using literature created by J.R.R. Tolkien. This approach was considered applicable, and findings support this way of language teaching. Findings show that when students are given the chance to be creative and have an opportunity to take part in the process of their education, they can exceed the expectations of the teacher and improve their language abilities. This study shows that by approaching language learning in this way an opportunity arises to combine language and content to enhance education in the future, both for teachers and students.